An exploratory study to understand the critical factors affecting the decision to adopt cloud computing in Taiwan hospital - Lian, Jiunn-Woei; Yen, David C.; Wang, Yen-Ting (International journal of information management, 2014)
•To investigate the factors to adopt cloud computing in Taiwan hospitals industry.•To integrate the TOE framework and HOT-fit model for the study.•A significant difference exist in CIO innovativeness, data security, compatibility.•Important dimensions are technology and then human, organization, and environment. The purpose of this study is to investigate the critical factors that will affect the decision to adopt cloud computing technology in developing countries, specifically in Taiwan's hospital industry. This study mainly integrates the TOE (Technology-Organization-Environment) framework and HOT-fit (Human-Organization-Technology fit) model to understand this issue. Information was collected by employing a questionnaire research design to hospital CIOs in Taiwan. The obtained results indicate that the 5 most critical factors are data security, perceived technical competence, cost, top manager support, and complexity. Further, among the proposed four dimensions the most important one is technology followed by human, organizational, and environmental factors. Finally, the results show that significant differences exist in CIO innovativeness, data security, compatibility, top manager support, adequate resource, and perceived industry pressure across different adopting groups. For practitioners, this study identifies key factors for hospitals to make an adoption decision toward cloud computing technology. As for academia, this study can be provided as a useful reference for future studies in this subject field.